2021
DOI: 10.3390/en14154658
|View full text |Cite
|
Sign up to set email alerts
|

Land Subsidence Estimation for Aquifer Drainage Induced by Underground Mining

Abstract: Land subsidence caused by groundwater withdrawal induced by mining is a relatively unknown phenomenon. This is primarily due to the small scale of such movements compared to the land subsidence caused by deposit extraction. Nonetheless, the environmental impact of drainage-related land subsidence remains underestimated. The research was carried out in the “Bogdanka” coal mine in Poland. First, the historical impact of mining on land subsidence and groundwater head changes was investigated. The outcomes of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 142 publications
1
5
0
Order By: Relevance
“…The variations of velocity at the maximum subsidence point can re ect the overall trend of workface subsidence (Guzy and Witkowski, 2021). After analysis in this study, it was found that the subsidence velocity of the working face generally showed a trend of rst increasing and then decreasing, which is consistent with related studies (Chen et al 2017).…”
Section: Subsidence Change Regularity In Different Periodssupporting
confidence: 89%
“…The variations of velocity at the maximum subsidence point can re ect the overall trend of workface subsidence (Guzy and Witkowski, 2021). After analysis in this study, it was found that the subsidence velocity of the working face generally showed a trend of rst increasing and then decreasing, which is consistent with related studies (Chen et al 2017).…”
Section: Subsidence Change Regularity In Different Periodssupporting
confidence: 89%
“…The Budryk-Knothe theory (Knothe 1983) was used for the analysis conducted in this paper due to its huge popularity in Poland [4,24,25] and in other countries [5,11,18,26,27]. Despite this popularity, it is worth providing the basic formulas for the extraction field of a rectangular shape.…”
Section: Analysis Methods Usedmentioning
confidence: 99%
“…Numerical methods that are gaining popularity due to the development of digital technology [17][18][19][20]. FLAC3D software is the most frequently used.…”
Section: Introductionmentioning
confidence: 99%
“…Even after mining activities have ceased, landscape deformation is a problem in many regions. Land surface deformation endangers human lives and property by causing severe damage to both buildings and transportation infrastructure (Guzy and Witkowski, 2021). Mining development causes serious damage to land resources.…”
Section: Introductionmentioning
confidence: 99%